Platelet-Dependent Inflammatory Dysregulation in Patients with Stages 4 or 5 Chronic Kidney Disease: A Mechanistic Clinical Study. Issue 12 (29th December 2022) - Corken, Adam; Ware, Jerry; Dai, Junqiang; Arthur, John M.; Smyth, Susan; Davis, Clayton L.; Liu, Juan; Harville, Terry O.; Phadnis, Milind A.; Mehta, Jawahar L.; Rahmatallah, Yasir; Jain, Nishank
Key Points: Patients with CKD have a reduced platelet count, higher platelet volume, reduced platelet-leukocyte interactions, and higher nonclassic monocytes. Platelet-derived cytokines are one of the central cytokines in correlation analysis of 45-cytokine panel in patients with stages 4 or 5 CKD. Antiplatelet drugs had multifaceted effects on thromboinflammation, suggesting platelet-dependent and -independent inflammation in CKD. Visual Abstract: Abstract : Background: Chronic kidney disease (CKD) is characterized by dysregulated inflammation that worsens with CKD severity. The role of platelets in modulating inflammation in stage 4 or 5 CKD remains unexplored. We investigated whether there are changes in platelet-derived thromboinflammatory markers in CKD with dual antiplatelet therapy (DAPT; aspirin 81 mg/d plus P2Y12 inhibitor). Methods: In a mechanistic clinical trial, we compared platelet activation markers (aggregation and surface receptor expression), circulating platelet-leukocyte aggregates, leukocyte composition (monocyte subtypes and CD11b surface expression), and plasma cytokine profile (45 analytes) of non-CKD controls ( n =26) and CKD outpatients ( n =48) with a glomerular filtration rate (GFR) <30 ml/min per 1.73 m 2 on 2 weeks of DAPT. Results: Patients with CKD demonstrated a reduced mean platelet count, elevated mean platelet volume, reduced platelet-leukocyte aggregates, reduced platelet-bound monocytes, higher total non-classic monocytes in the circulation, and higher levels of IL-1RA, VEGF, and fractalkine (all P <0.05). There were no differences in platelet activation markers between CKD and controls. Although DAPT reduced platelet aggregation in both groups, it had multifaceted effects on thromboinflammatory markers in CKD, including a reduction in PDGF levels in all CKD individuals, reductions in IL-1 β and TNF- α levels in select CKD individuals, and no change in a number of other cytokines. Significant positive correlations existed for baseline IL-1 β, PDGF, and TNF- α levels with older age, and for baseline TNF- α levels with presence of diabetes mellitus and worse albuminuria. Mean change in IL-1 β and PDGF levels on DAPT positively correlated with younger age, mean change in TNF- α levels with higher GFR, and mean changes in PDGF, and TRAIL levels correlated with worse albuminuria. Minimum spanning trees plot of cytokines showed platelet-derived CD40L had a large reduction in weight factor after DAPT in CKD. Additionally, platelet-derived IL-1 β and PDGF were tightly correlated with other cytokines, with IL-1 β as the hub cytokine. Conclusions: Attenuated interactions between platelets and leukocytes in the CKD state coincided with no change in platelet activation status, an altered differentiation state of monocytes, and heightened inflammatory markers. Platelet-derived cytokines were one of the central cytokines in patients with CKD that were tightly correlated with others. DAPT had multifaceted effects on thromboinflammation, suggesting that there is platelet-dependent and -independent inflammation in stage 4 or 5 CKD.